2003
DOI: 10.1007/s00249-003-0296-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field induced transmembrane potential on spheroidal cells: theory and experiment

Abstract: The transmembrane potential on a cell exposed to an electric field is a critical parameter for successful cell permeabilization. In this study, the effect of cell shape and orientation on the induced transmembrane potential was analyzed. The transmembrane potential was calculated on prolate and oblate spheroidal cells for various orientations with respect to the electric field direction, both numerically and analytically. Changing the orientation of the cells decreases the induced transmembrane potential from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
131
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(145 citation statements)
references
References 23 publications
13
131
0
1
Order By: Relevance
“…In addition, in vitro and in vivo studies have elucidated the effect of the shape, size and orientation of cells in tissue and cell density on electric field distribution, which are all crucial factors for effective electrotransfection. 24,26,30 We pointed out in a recent study 26 that the histological properties of tumors are responsible for different transfection efficiencies obtained and this may also be true for the different transfection efficiencies obtained in different tissues using the same electric pulse parameters.…”
Section: Electrotransfer Of Tumors M Cemazar Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in vitro and in vivo studies have elucidated the effect of the shape, size and orientation of cells in tissue and cell density on electric field distribution, which are all crucial factors for effective electrotransfection. 24,26,30 We pointed out in a recent study 26 that the histological properties of tumors are responsible for different transfection efficiencies obtained and this may also be true for the different transfection efficiencies obtained in different tissues using the same electric pulse parameters.…”
Section: Electrotransfer Of Tumors M Cemazar Et Almentioning
confidence: 99%
“…Field effects are dependent on cell shape and size, the orientation of the cells versus the field orientation and the composition of the tissue. [24][25][26] Nevertheless, it has been suggested that the function of 'HV' and 'LV' pulses is the same for both tissues, the 'HV' pulse permeabilizes target cells and the 'LV' pulse electrophoretically transports the DNA to the cells.…”
Section: Introductionmentioning
confidence: 99%
“…30 On the other hand, in vitro studies have exposed the effect of the shape, size and orientation of cells in tissue and cell density. 31,32 Therefore, an important challenge for efficient gene therapy in solid tumors is to identify the structural and physiological properties of the tumor tissue. Better understanding of tissue barriers might be useful for the prediction of transgene expression patterns in certain tumor types in vivo, as well as for further optimization of gene delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies added more complexity to the modeled cell and provided insight into the factors affecting the induced transmembrane potential. This included both the electrical [5,[9][10][11][12] and geometrical properties of the cell, such as its shape [13,14] and orientation to the field [15,16]. These works stressed the importance of cellular properties in the build-up of the transmembrane potential.…”
Section: Introductionmentioning
confidence: 99%